GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR MAPPING GREENPARK USING LEAFLET JS - Muhammad Zakki Abdillah; Devi Astri Nawangnugraeni; Abdul Hakim Prima Yuniarto (STMIK KAPUTAMA, 2021)
Geographical Information System (GIS) is one of systems that functions to process spatial data so that it becomes information that can be understood by ordinary people. Leafletjs is one of the technologies in the development of Geographical Information Systems based online and open source, so the development more dynamic and flexible. This stud present the processing of spatial data into an online-based Geographical Information System. The database used in this development includes Green Space which is divided into 2 classifications, namely Public and Private, and there are 738 total data. With the large amount of data it is possible to process informatively using web-based Geographical Information System using Leafletjs technology. The results of the research, resulting in a percentage of 19.61% data on public greenpark, this results almost the minimum standards for greenpark in an area. So with the web-based information system, people can see the greenpark data in the form of a digital map that easy to understand because it is presented on a polygon map.